Effect of Laser Cleaning and Hyperpassivation on the Electrochemical Behavior of AA2024-T3. Issue 3 (1st March 2021) - McFall-Boegeman, Sarah; Yancey, David F.; O'Neill, Tyler; Davidson, Nick; Swain, Greg M.
Abstract : Environmentally sustainable surface pretreatments and coating systems are needed in the aerospace industry. Laser cleaning is one such surface pretreatment method that reduces the need of hazardous chemicals, and their associated monitoring and disposal, for cleaning metal parts. Research was conducted to investigate how two laser surface pretreatments, (i) cleaning and (ii) hyperpassivation, affect the electrochemical behavior of aluminum alloy 2024-T3. The difference between the two pretreatments was the laser fluence per pulse, 5.2 (cleaning) vs 10.8 J cm −2 (hyperpassivation), respectively. Comparison studies were performed using specimens pretreated by standard wet chemical cleaning and deoxidation. The laser pretreated and solution processed specimens were characterized using electrochemical methods, digital optical microscopy, optical profilometry, scanning electron microscopy, and depth profiling X-ray photoelectron spectroscopy. The laser cleaning and hyperpassivation pretreatments both clean the surface and improve the corrosion resistance of this alloy in naturally aerated 0.5 M Na2 SO4, as compared to the solution processed specimen. This is evidenced by suppressed anodic and cathodic polarization curve currents, increased polarization resistance, and increased low frequency impedance modulus values. The improved corrosion resistance results from the formation of a thicker and presumably less defective oxide layer on the aluminum and reduced exposure of Cu-rich second-phase particles.